Men against the sea - Nordhoff, Charles, 1887-1947; Hall, James Norman, 1887-1951 (Boston : Little, Brown, and Company, 1934)
Unsurpassed as a gripping tale of historical adventure, Men Against the Sea is the epic account of the eighteen loyal men set adrift on the high seas after the mutiny on the Bounty. With Captain Bligh at the helm of a 23-foot open launch, the loyal sailors are alone on uncharted waters, struggling to survive on scant rations and taking pains to avoid war canoes and inhabited islands under cover of night. Their 3,600-mile voyage from the island of Tofoa in the Friendly Archipelago to the Dutch East Indies remains to this day one of the greatest feats of courage and endurance in maritime history.
Maps on lining-papers.
A continuation of Mutiny on the Bounty.
Keywords: Bligh, William, -- 1754-1817 -- Fiction; Bligh, William, -- 1754-1817; 1900-1999; Sea stories -- 20th century; Sea stories; Great Britain -- History, Naval -- 18th century -- Fiction; Fiction; Sea stories; Fiction; Sea fiction; Sea stories